Blood clot contraction: Mechanisms, pathophysiology, and disease - Litvinov, Rustem I.; Weisel, John W. (Research and practice in thrombosis and haemostasis, 2023)
A State of the Art lecture titled “Blood Clot Contraction: Mechanisms, Pathophysiology, and Disease” was presented at the International Society on Thrombosis and Haemostasis (ISTH) Congress in 2022. This was a systematic description of blood clot contraction or retraction, driven by activated platelets and causing compaction of the fibrin network along with compression of the embedded erythrocytes. The consequences of clot contraction include redistribution of the fibrin-platelet meshwork toward the periphery of the clot and condensation of erythrocytes in the core, followed by their deformation from the biconcave shape into polyhedral cells (polyhedrocytes). These structural signatures of contraction have been found in ex vivo thrombi derived from various locations, which indicated that clots undergo intravital contraction within the blood vessels. In hemostatic clots, tightly packed polyhedrocytes make a nearly impermeable seal that stems bleeding and is impaired in hemorrhagic disorders. In thrombosis, contraction facilitates the local blood flow by decreasing thrombus obstructiveness, reducing permeability, and changing susceptibility to fibrinolytic enzymes. However, in (pro)thrombotic conditions, continuous background platelet activation is followed by platelet exhaustion, refractoriness, and impaired intravital clot contraction, which is associated with weaker thrombi predisposed to embolization. Therefore, assays that detect imperfect in vitro clot contraction have potential diagnostic and prognostic values for imminent or ongoing thrombosis and thrombotic embolism. Collectively, the contraction of blood clots and thrombi is an underappreciated and understudied process that has a pathogenic and clinical significance in bleeding and thrombosis of various etiologies. Finally, we have summarized relevant new data on this topic presented during the 2022 ISTH Congress. •Platelet-driven contraction (retraction) of blood clots/thrombi is a physiologic mechanism.•The contraction causes a redistribution of clot components and compressive deformation of RBCs.•Contraction in (pro)thrombotic states is impaired due to the exhaustion of hyperactivated platelets.•Contraction of thrombi affects obstructiveness, permeability, fibrinolysis, and embologenicity.